N-Heterotriangulenes: Fascinating Relatives of Triphenylamine - Hammer, Natalie; Schaub, Tobias; Meinhardt, Ute; Kivala, Milan (Chemical Record, 2015)
Carbonyl- and dimethylmethylene-bridged triphenylamines called N-heterotriangulenes are not only aesthetically pleasing extgreekp-conjugated scaffolds interesting on their own but also provide numerous possibilities for further synthetic modifications to serve as versatile precursors for the construction of functional organic molecules. In this Personal Account we give a historical synopsis depicting the long way from the initial synthesis of N-heterotriangulenes back in the 1970s to their derivatization followed by recent applications in organic electronics. As a part of our ongoing research on heteroatom-doped extgreekp-conjugated scaffolds we provide an overview of our synthetic efforts involving the N-heterotriangulene scaffolds and discuss the optoelectronic, redox, and self-assembly properties of the resulting molecular entities.
EAM Import::2019-03-12